Profil Kemampuan Komunikasi Mahasiswa Pendidikan Fisika Universitas Mataram Menggunakan Presentation Skills Rubric Cornell University - Fathurrahman; Hikmawati (Mataram University, 2026)
Public speaking ability is a crucial interpersonal competency that must be mastered by pre-service teachers as a foundation for future classroom management. This study aims to map the academic communication skills of fifth-semester students in the Physics Education Study Program at Universitas Mataram in the course of School Administration and Management (AMS). The research employed a descriptive quantitative method using structured direct observation of 54 students. The data collection instrument was an observation sheet adapted from the Presentation Skills Rubric developed by Cornell University, which includes four dimensions: Content, Organization, Delivery, and Visual Media. The results revealed a significant performance imbalance across the assessed dimensions. Students demonstrated very strong performance in Visual Media (3.50) and Content (2.80). However, the Delivery dimension declined sharply to 2.15 (low category). As many as 59.2% of students (32 individuals) were categorized as “very poor” in eye contact due to a high dependency on reading text from slides. The theoretical and regulation-heavy characteristics of AMS course materials encouraged students to rely on reading rather than engaging in visual interaction with the audience. These findings highlight the need for methodological interventions in teaching, such as mind mapping training and the use of transparent assessment rubrics from the beginning of the semester, to better prepare competent pre-service physics teachers in pedagogical communication skills.